Current global status of dengue diagnostics - D. Smith, Miranda; Azizan, Azliyati (Journal of Advances in Biology & Biotechonology, 2014)
Dengue Virus is a re-emerging infectious disease that is transmitted through mosquitos. Dengue is a significant health concern because of the number of people it affects globally. Clinical diagnosis of dengue is not possible because the symptoms are similar to other febrile-diseases. Therefore, the only way to truly diagnose dengue is via laboratory methods. Many diagnostics tests exist to accomplish this; however, these tests have disadvantages. Rapid, point-of-care, commercially available diagnostic test kits have come onto the market to bridge the gap for those without high tech laboratories and personnel. This paper extends the knowledge of a meta-analysis conducted in 2011 on the performance of commercially available diagnostic tests. The purpose of this review was to compare and contrast the accuracy of commercial dengue diagnostic tests.
Keywords: dengue; diagnostics; commercial; rapid; point-of-care; tests